2004
DOI: 10.1097/01.brs.0000116990.31984.a9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Traumatic Fractures of the Thoracic and Lumbar Spine

Abstract: In general, surgical treatment of traumatic spine fractures is safe and effective. Surgical techniques can only be compared using randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(155 citation statements)
references
References 145 publications
5
140
0
10
Order By: Relevance
“…A total of 17.7% from the cohort of patients with AS and 20.0% from the patients with DISH deceased within 3 months after injury whereas the previously reported mortality in individuals treated surgically for traumatic spinal fractures was only 0.4% [124]. The mortality in the follow-up phase was higher in DISH patients than in AS patients, regardless of type of treatment received.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A total of 17.7% from the cohort of patients with AS and 20.0% from the patients with DISH deceased within 3 months after injury whereas the previously reported mortality in individuals treated surgically for traumatic spinal fractures was only 0.4% [124]. The mortality in the follow-up phase was higher in DISH patients than in AS patients, regardless of type of treatment received.…”
Section: Discussionmentioning
confidence: 78%
“…Worsening of neurological function due to inadequate immobilization, inconsiderate transfers or application of a hard collar on the cervical spine with pre-existing kyphotic deformity was reported in several articles [68,74,89,122]. Compared to studies describing (healthy and considerably younger) individuals sustaining traumatic spine fractures where only 0.08% of the patients deteriorated in neurological function, these numbers are of major concern [124]. It is suggested that patients with traumatic fractures of the ankylosed spine are not only susceptible to initial neurological deficit but also to secondary neurological deterioration due to highly unstable fracture configurations between the fused segments [11].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of this technique include less surgical dissection, blood loss, and time in surgery, and as a result, decreased perioperative morbidity. However, loss of reduction and instrumentation failure associated with this technique is well described in the literature 159. These failures have been attributed to poor bone quality, inadequate anterior column support, and insufficient points of fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior transpedicular pedicle screw fixation is widely used for obtaining internal fixation for management of the unstable spine mainly caused by trauma, and burst fractures comprise 10–20% of such injuries 1. The aims of surgery in these fracture cases include decompression of the neural components, fracture reduction, and providing a stable fixation until arthrodesis is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…К причинам возникно-вения посттравматических деформа-ций относят неадекватно применен-ный метод консервативного лечения, позднее выявление переломов позво-ночника вследствие тяжести политрав-мы, сочетанной травмы, недиагности-рованные и нелеченные переломы позвонков [17,24].Посттравматические деформации приводят к нарушению сагиттального баланса туловища и возникновению болевых синдромов, функциональной несостоятельности грудного, пояснич-ного отделов позвоночника и космети-чески неприемлемых деформаций [18]. …”
unclassified